Molecular Mechanisms of Synergistic Effect of PRIMA‐1met and Oxaliplatin in Colorectal Cancer With Different p53 Status - Xiao‐lan Li; Jianbiao Zhou; Nicole Xin‐Ning Tang; Yi Chai; Meng Zhou; Ai‐di Gao; Zhong‐kai Lu; Han Min (Cancer Medicine)
ABSTRACT Background The toxicity and drug resistance associated with oxaliplatin (L‐OHP) limit its long‐term use for colorectal cancer (CRC) patients. p53 mutation is a common genetic trait of CRC. PRIMA‐1met (APR‐246, eprenetapopt) restores the DNA‐binding capacity of different mutant P53 proteins. PRIMA‐1met has progressed to the Phase III clinical trial. Our study explores the combination therapy of PRIMA‐1met and L‐OHP for CRC with different p53 status. Methods Cell viability was assessed with Cell Counting Kit‐8 (CCK‐8) assay and combination index (CI) was calculated using The Chou‐Talalay method. We also employed wound healing assay and colony formation assay to determine the effect of L‐OHP, PRIMA‐1met and their combination. Weighted gene co‐expression network analysis (WGCNA) of RNA‐seq data was conducted to identify key modules and central genes related to different treatment modalities. Xenograft CRC mouse model was used to assess the combination treatment in vivo. Results Our findings showed heightened cytotoxicity and inhibition of migration, and colony formation in CRC cells treated with both drugs, irrespective of p53 status, presenting a promising avenue for addressing L‐OHP resistance and toxicity. RNA‐seq analysis revealed differential responses between p53‐wide type HCT116 and p53‐mutant DLD‐1 cells, with pathway alterations implicated in tumorigenesis. WGCNA identified key modules and hub genes associated with combination therapy response. In vivo studies demonstrated enhanced efficacy of combined therapy over PRIMA‐1met alone, while mitigating L‐OHP‐induced toxicity. Conclusions In summary, our research reveals the differential molecular mechanisms of combined PRIMA‐1met and L‐OHP in CRC with wild type p53 and mutant p53. Our data not only demonstrate that this combined regimen exerts synergistic anti‐CRC effect in vitro and in vivo, but also suggest the benefit of PRIMA‐1met on prevention of L‐OHP‐related side effects. These findings underscore the clinical potential of PRIMA‐1met‐L‐OHP combination therapy in CRC, offering enhanced efficacy and reduced toxicity, warranting further clinical investigation.